Morphometric, meristic and growth patterns of (Thynnichthys thynnoides Bleeker, 1852) from the Pinang Luar Oxbow Lake, Buluhcina Village, Kampar Regency, Riau Province - Nofika Srijayanti; Ridwan Manda Putra; Deni Efizon (Jurnal Online Mahasiswa (JOM) Bidang Perikanan dan Ilmu Kelautan, 2016)
Thynnichthys thynnoides or motan fish is freshwater fish that inhabit the Pinang Luar Oxbow Lake. This fish has high economical value, around Rp. 25.000- 35.000 /kg. To understand the morphometrical, meristical characteristics and growth pattern of this fish, a research had been conducted from March-May 2016. There were 149 fishes (75.04-181.57 mm TL and 3,78-53,77 gr BW) were captured from the lake. There were 26 morphological characteristics measured and 9 meristical characteristics counted. General body form of the fish is not changing as the fish growing. The meristical characteristics of the fish were as follow : D.I.27-29, P.10.5, V.II.5-8, A.5-7.2, C.10-12.9, the number of scale in the pre-dorsal fin 45-50, around the body was 46-48, the caudal peduncle was 12-14 and the lateral line was 58-60. The length-weight relationship shown that the growth of male is negative allometric (b= 2.975), but that of the female was positif allometric (b= 3.092). The water quality parameters shown that temperature 26-280C, transparency 22-49 cm, pH 6, DO 4.6-6.2 mg/L, CO2 5.8-8.5 mg/L and depth 108-520 cm. Data on water quality parameters indicate that water quality in the Pinang Luar Oxbow Lake is able to support the life of the motan fish.Keywords : Thynnichthys thynnoides, Pinang Luar Oxbow Lake, morphometric, meristic, growth patterns